Reduction in life activities after hospitalization for COVID-19 in intensive care units - Martins , Hevelyn Mayara Traleski; Amaral, Ianka do; Souza , Thayná Kimberly Pereira de; Duarte , Carolina Ribeiro; Schiochet, Gabriela Fernanda; Fadel, Cristina Berger; Santos, Celso Bilynkievycz dos (Revista de Enfermagem da UFPI, 2024)
Objective: To verify the factors associated with reduction in life activities in patients 12 months after discharge from the COVID-19 ICU. Methods: This is a cross-sectional, analytical study with a quantitative approach, based on primary data from patients at the Hospital Universitário Regional dos Campos Gerais, Paraná, Brazil. The final sample consisted of 32 patients discharged from the ICU between March 2020 and March 2021. Results: There was statistical evidence of a difference between the means of the groups in the domains Life Activities (p= 0.0001) and Disability (p< 0.0001), confirming that the disabled group has a worse indicator of disability in this domain; as also occurs between the geometric means of the groups. Conclusion: The most prevalent factors associated with reduction in life activities were those involving the physical and psychological domains, directly influencing their recovery. In addition, future research could focus on specific intervention strategies to minimize the impact of these sequelae and improve rehabilitation in COVID-19 patients.